Neuroenergetics of traumatic brain injury - Kate Karelina; Zachary M Weil (Concussion)
A subset of traumatic brain injury (TBI) patients exhibit cognitive deficits later in life which may be due to the underlying pathology associated with Alzheimer's disease (AD) or chronic traumatic encephalopathy. The similarities between chronic traumatic encephalopathy and AD merit investigation of potentially similar mechanisms underlying the two diseases. Experimental and clinical studies of AD brains have revealed that insulin resistance links metabolic dysfunction to the neurodegeneration and cognitive deficits associated with AD. Recent work in experimental TBI has established that recovery is dependent on the return of normal brain metabolism and mounting evidence for a role of brain insulin in regulating central metabolism suggests that TBI, like AD, results in central insulin resistance. Here, we review the converging evidence from AD, TBI and diabetes research linking insulin insensitivity to neurodegeneration.